2015
DOI: 10.1055/s-0035-1555753
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism Might Increase the Risk of Postoperative Atrial Fibrillation after Aortic Valve Replacement

Abstract: Background To evaluate the influence of subclinical hypothyroidism (SCH) on the development of postoperative atrial fibrillation (AF) in patients undergoing aortic valve replacement surgery with extracorporeal circulation. Methods A prospective study in a tertiary hospital between July 2005 and December 2013 in which all patients undergoing aortic valve replacement with no other valve surgery were consecutively included. Patients who were in preoperative sinus rhythm were selected and they underwent thyroxine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Although a recent study revealed a possible association of subclinical hypothyroidism with AF/AFL [66], our study, consistent with another study using the Framingham Heart Study participants [67], did not show such an association. Inconsistent with previous studies [68, 69], we did not find a significant association between hypothyroidism or sleep apnea and AF.…”
Section: Discussionsupporting
confidence: 88%
“…Although a recent study revealed a possible association of subclinical hypothyroidism with AF/AFL [66], our study, consistent with another study using the Framingham Heart Study participants [67], did not show such an association. Inconsistent with previous studies [68, 69], we did not find a significant association between hypothyroidism or sleep apnea and AF.…”
Section: Discussionsupporting
confidence: 88%
“…In HVS patients, the mortality rates were similar regardless of TSH levels, providing further supporting that the risk associated with higher TSH levels was not related to cardiac surgery, but to conditions associated with high cardiovascular risk. Regarding the associations of thyroid dysfunction in patients undergoing HVS, Martinez-Comendador et al [ 18 ] reported that SCH was associated with an increased risk of postoperative Afib in patients undergoing aortic valve replacement, but there were limited data on the long-term outcomes of HVS patients according to thyroid function. We did not find any significant effects of SCH on postoperative outcomes in the HVS group, although the number of subjects might not have been sufficient to fully elucidate the impact of SCH on the long-term prognosis in patients with HVS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not confirm whether the poor outcomes of SCH patients were specific to CABG or would be similar after other cardiac surgical procedures in patients whose cardiovascular risk is not as high. A previous study showed increased postoperative Afib in SCH patients after aortic valve replacement surgery [ 18 ], although they did not present long-term outcomes after surgery.…”
Section: Introductionmentioning
confidence: 96%
“…Atrial enlargement may occur as a consequence of AF (37,38), and LA enlargement preceding AF or higher LAD may lead to an increased risk of incidence and recurrence of AF (39)(40)(41)(42). Additionally, overt and subclinical hypothyroidism has been demonstrated to increase the risk of postoperative AF in the patients underwent cardiac surgery (43)(44)(45). However, our study matched AF in the PS analyses, which indicated that the difference of LAD between hypothyroidism and euthyroid groups was independent of AF.…”
Section: Discussionmentioning
confidence: 57%